Pola Rekrutmen Penyelenggara Pemilihan Umum Tingkat Kelompok Penyelenggara Pemungutan Suara Di Kecamatan Medan Selayang Pada Pemilihan Umum Serentak Tahun 2019 - Andi Elkana Ginting; M. Arif Nasution; Heri Kusmanto (Universitas Medan Area, 2021)
The purpose of this research is to know and analyze the recruitment process, the impact of the recruitment pattern of the election organizers at the level of the Voting Organizing Group in Medan Selayang District, Medan City on the Integrity of the 2019 Concurrent General Elections. The form of this research is qualitative research with descriptive analysis, to describe and explains in depth the recruitment pattern of election organizers for the Voting Organizing Group (KPPS) which is the spearhead of the implementation of voting and counting of votes in the 2019 Election. The impact of the recruitment pattern of general election organizers at the KPPS level in Medan Selayang District, Medan City on the Integrity of the General Election Concurrent Years 2019, linked by scrutiny, has had a positive impact. Supervision from Bawaslu that has been getting better, the rules and implementing regulations set by the KPU are detailed. Bawaslu already has a very good system. This supervision plays an important role in its implementation to maintain the code of ethics of the organizers, one of which is integrity. The positive impact is evident from the fact that KPPS Medan Selayang is able to carry out its duties properly, following established procedures and regulations, there are no reports of complaints, either from Bawaslu, witnesses from parties / pairs of candidates, or the public. The election activities were carried out in an orderly and conducive manner, according to schedule, and the counting of votes was transparent. KPPS is wise. The public can exercise their voting rights in an orderly and comfortable manner. TPS locations are well prepared. Good approach and communication with local residents.